WHAT TEACHERS’ BELIEFS ON TEACHING? AN EXPLORING STUDY OF HIGH SCHOOL TEACHERS - Cut Aulia Maksum; Marty Mawarpury (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2016)
Belief plays an important role in many aspects of teaching, it influences the way of teachers to make decisions and actions in the classroom. What teachers believe about teaching-learning becomes central to determining their actual behavior towards students and education in general. This study aims to find the beliefs of teachers about their profession. The data were collected by in-depth interview of three different subject teachers at SMA 6 Lhokseumawe. The study found that teachers' beliefs cannot always take into practice. Teachers believe that they are the key stakeholder for bringing better education, unfortunately, context and situation like educational system is a big dilemma for teachers to put their beliefs into classroom practice. The result of this study also revealed that all of the teachers are committed to their profession; two participants confessed that they never dreamt of being a teacher but they decided to be a teacher because of some reasons. Besides, all participants have committed not to shift their profession someday.